2012
DOI: 10.1002/14651858.cd009600
|View full text |Cite
|
Sign up to set email alerts
|

Ergonomic positioning or equipment for treating carpal tunnel syndrome

Abstract: Analysis 1.2. Comparison 1 Ergonomic keyboard versus placebo keyboard, Outcome 2 Short-term improvement in CTS symptoms (Phalen test time (seconds)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 40 publications
0
19
0
7
Order By: Relevance
“…Separate reviews of non-surgical interventions have replaced an original Cochrane Review of non-surgical treatment (other than steroid injection) (O’Connor 2003). Current Cochrane Reviews of non-surgical treatment for CTS include reviews of corticosteroid injection (Marshall 2007), surgical versus non-surgical treatment (Verdugo 2008), therapeutic ultrasound (Page 2013), exercise and mobilisation interventions (Page 2012a), splinting (Page 2012b), ergonomic positioning or equipment (O’Connor 2012), and low-level laser therapy (Rankin 2017). Acupuncture has been recommended as a potentially useful treatment for CTS (Morey 1998), but its effectiveness remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Separate reviews of non-surgical interventions have replaced an original Cochrane Review of non-surgical treatment (other than steroid injection) (O’Connor 2003). Current Cochrane Reviews of non-surgical treatment for CTS include reviews of corticosteroid injection (Marshall 2007), surgical versus non-surgical treatment (Verdugo 2008), therapeutic ultrasound (Page 2013), exercise and mobilisation interventions (Page 2012a), splinting (Page 2012b), ergonomic positioning or equipment (O’Connor 2012), and low-level laser therapy (Rankin 2017). Acupuncture has been recommended as a potentially useful treatment for CTS (Morey 1998), but its effectiveness remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…This position is expected to cause least pressure on the median nerve theoritically. While there some ergonomic advise for protecting wrist from CTS, there is no strong evidence for or against the use of ergonomic keyboards for the treatment of CTS (25) . The difference that found between the groups in our study was associated only with repetitive wrist movement.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsurgical treatments include splinting and ergonomic interventions. The most important feature of these non-surgical treatments is that the hand is used with the wrist positioned in a neutral position 6) . Several ergonomic studies have reported that the use of devices as well as assessment tools and interventions can re-educate wrist posture 7) .…”
Section: Discussionmentioning
confidence: 99%